Impacts of trade liberalization in Canada's supply managed dairy industry. (26th May 2020) - Biden, Scott; Ker, Alan P.; Duff, Stephen
Abstract: Trade is an integral part of the Canadian economy. The main institutional drivers governing trade are bilateral and multilateral agreements outlining permissible trade distorting measures. Since its inception in 1972, Canada's supply management system has remained protected throughout trade negotiations. The system appears, by any economic measure, to be having an increasingly disproportional influence in recent trade negotiations. However, trade agreements serve not only to maximize social surplus, but also to maximize some measure of political welfare. Canada has recently negotiated three prominent trade agreements: the Canada‐European Union Comprehensive Economic and Trade Agreement (CETA) came into effect in the latter part of 2017; the Comprehensive and Progressive Agreement for Trans‐Pacific Partnership (CPTPP) came into effect at the end of 2018; and the Canada‐United States‐Mexico Agreement (CUSMA) could come into effect in 2020. Collectively, these agreements have guaranteed increased market access for fresh and processed dairy products. We build a spatial partial equilibrium model of the Canadian dairy industry consisting of three regions and 10 commodities to assess the individual and cumulative effect of these trade agreements. We pay particular attention to the institutional drivers within today's dairy sector: milk protein isolates; component pricing, including Class 7; and differential demand growth. We find that the aggregate impacts are: (a) a 1.4% decrease in the marginal retail price; (b) a 4.8% decrease in the blended producer price; and (c) an overall increase in social welfare of 7.8%. Worth noting, the decrease in producer surplus varies from 0.7% in the western region to 1.5% in Ontario. Our results may be relevant to future negotiations as well as the publicly promised compensation package for dairy producers.